Book Reviews. Issue 1 (1st May 2018) - Sticchi, Francesco; Wilson, Gavin
Teorie del Cinema: Il Dibattito Contemporaneo, Adriano D'Aloia and Ruggero Eugeni (eds) (2017) Milano: Raffaello Cortina Editore, 408 pp., ISBN: 9788860309587, p/bk, €35.00Bodies in Suspense: Time and Affect in Cinema, Alanna Thain (2017) Minneapolis and London: University of Minnesota Press, 328 pp., ISBN: 978-0-8166-9295-8, p/bk, 30.00; ISBN: 978-0-8166-9293-4, h/bk, 120.00